(untitled) (Bangladesh Journal of Zoology, 2020)
A total of 900 female inhabitants of lower socioeconomic in Dhaka city, were examined during September, 2013 to August, 2015. Among them, the prevalence of gastrointestinal parasitic infestation was 66.22%. The prevalence of Urinary tract infection (UTI) was 31.44%. Among the female inhabitants, 41.33% were infected with different types of skin diseases; within these, viral, (19.35%) scabies and 38.09% were affected by boil disease. The prevalence of vector-borne diseases was infected and arthropod infections (9.41%) were found. Among them, the highest 54.28% were infected by scabies and 38.09% were affected by boil diseases. The prevalence of vector-borne diseases was 49.33%, among them four types of diseases were recorded of which 2% malaria, 7.33% filaria, 34.67% dengue and 5.33%. leishmaniasis. Four types of waterborne diseases were found such as cholera/ diarrhoea (28%), typhoid (17.11%), polio (5.11%) and hepatitis A/ Jaundice (9.67%); and overall prevalence was 59.87%. Regarding the airborne diseases, 58.44% were found to be infected, among them four types recorded, such as influenza (25.11%), mumps (10.22%), pneumonia (17.44%) and tuberculosis (5.67%). Bangladesh J. Zool. 48(1): 105-117, 2020